PREPARATION OF INFILTRATION WELL DEVELOPMENT PLANNING IN KADIRI UNIVERSITY AREA - Sony Susanto; Ahmad Ridwan; Sigit Winarno; Yosef Cahyo Setianto (CI-TECH, 2021)
Along with the development in Indonesia, resulting in the reduction of vacant land used as water infiltrated into the ground. This causes frequent flooding such as at Kadiri University, Kediri City there are often flood puddles when rainfall is high. To overcome this disaster, it is necessary to create infiltration wells in the area because the infiltration wells are so effective, and practical. This study aims to overcome or overcome puddles at Kadiri University. The metodologi penelitian is carried out in several stages, namely the primary and secondary data collection stage, the second processing of parametric testdistributiondata, the third calculation of water discharge and smirnov kolmogrov test, thefourth determination of the dimensions of infiltration wells. The final result of the analysis obtained sage of infiltration in the form of a circle with a diameter of 1.4 meters depth of 3 meters a number of 153 pieces. Dengan the existence of infiltration wells later is expected to reduce puddles in the campus area.